A tradução da personagem Elizabeth Bennet, de Pride & Prejudice, para o cinema. - Silva, Ricelly Jáder Bezerra da (2014)
This dissertation aims at analyzing the process of translating the character of Elizabeth Bennet, protagonist of the novel Pride & Prejudice, first published in 1813 by the English author, Jane Austen, into the film version Pride & Prejudice (1940), by Robert Z. Leonard. In her novel, Austen criticizes sociocultural patters which relegate women to an inferior position in relation to the male sex. Such criticism is subtlety present in the narrative and, especially, in the character of Elizabeth Bennet, who is seen as an intelligent, ironic and decisive woman. These qualities differ from the moral idea of women in nineteenth-century England. The presentation of this type of female character assures her of a timeless quality which is transmitted to posterity by means of translations. Pride & Prejudice was first translated for the Hollywood film in 1940, in the above mentioned Leonard’s version. Since the cinema is a medium that reaches a large audience of both readers and non-readers of literary works, one may question the strategies that are implied in the translation process of such character to the silver screen. It may be correctly assumed that when thus translated, any social criticism presented by the principal literary character tends to give way to a narrative which proposes entertainment, focusing on the love and comical relationship between the protagonists of the novel. The theoretic basis for the present analysis is based on the following concepts of translation: Lefevere’s translation rewriting (2007) and Cattrysse’s postulate (1995) which conceives film adaptation as a type of translation. Concerning film adaptation, Martin (2005), Eisenstein (2002) and McFarlane’s (2010) studies, which regard cinema as a linguistic art in its own right, were incorporated into our analysis as were those of Candido (2011), Rosenfeld (2011), Bakhtin (2011), Gomes (2011) and Forster (2004), all of whom discuss the structure of the fictional character. Such studies have resulted in a new configuration of the cinematographic character. Based on the criteria on the target system, this configuration permits the deleting of the critical level found in the universe of the novel and introduces the original work to a wider audience, as can be proved by the republishing of the novel in various editions after the release of the film version in 1940.